Influence of Climate and Justice on Commitment Organizational with Job Satisfaction as Intervening Variable at Regional Revenue Agency Denpasar City - Putra, I Gusti Made Oka Diara; Sapta, I Ketut Setia; Suardhika, I Nengah (Asia Pacific Journal of Management and Education (APJME), 2021)
Employee commitment is influenced by organizational climate and fairness to be able to grow and develop within an organization. The purpose of this study was to analyze and determine the effect of organizational climate and organizational justice on organizational commitment, with job satisfaction as an intervening variable at the Denpasar City Revenue Service. The hypotheses proposed based on existing theoretical studies and the existence of the phenomena summarized in the problem formulation are: organizational commitment is positively affected by organizational climate; organizational justice has an effect on organizational commitment as positively; organizational climate has an effect on job satisfaction as positively; job satisfaction is positively influenced by fairness organization; and organizational commitment is positively effected by job satisfaction. The design of this research system is oriented to the pattern of calculating quantitative data on the existence of questionnaires distributed to 83 respondents. The data used are primary and secondary data both qualitative and quantitative which are then analysed by PLS-based SEM, while the results found are as follows: organizational commitment is positively and significantly affected by organizational climate; organizational justice has an effect on organizational commitment is positively and significantly; job satisfaction is positively and significantly affected by organizational climate; organizational justice has an effect on organizational justice is positively and significantly; and organizational commitment is positively and significantly influenced by job satisfaction.